Pendampingan Individu Calon Guru Penggerak Angkatan 9 Kabupaten Enrekang - Ismaya Ismaya; Andi Ahmad Chabir Galib; Elihami Elihami; M. Yunus Sudirman (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Motivating Teachers is an educational program from the government to improve teacher competency. Apart from that, the presence of mobilizing teachers is expected to be able to mobilize the learning community. The principle of the program is to encourage efforts to improve the quality of education in schools and outside schools using andragogy and blended learning approaches. This activity was carried out with the aim of providing individual assistance to Prospective Mobilizing Teachers before they carry out workshop activities. The activity will last for 5 days, namely from 11-15 September 2023 which will take place face to face in five (5) schools, namely: SD Negeri 13 Curio, SD Negeri 147 Pelali, SMP Muhammadiyah Cece, SD Negeri 140 Kabere, SD Negeri 165 Pudete and SD Negeri 85 Laba. The results of the mentoring activities are: CGP is able to discuss online learning challenges; CGP was able to reflect on the implementation of class changes according to Ki Hajar Dewantara's thoughts; CGP is able to carry out discussions on creating a portfolio framework; and CGP is able to discuss self-position maps and self-development plans within the competence of driving teachers.